Effect of steel slag and curing temperature on the improvement in technological properties of biomass bottom ash based alkali-activated materials. (4th October 2021) - Gómez-Casero, M.A.; Pérez-Villarejo, L.; Castro, E.; Eliche-Quesada, D.
Graphical abstract: Highlights: Replacing BBA with BSS by 50 wt% increased mechanical properties. Alkali-activated cements using BBA and BSS show high strength after curing at 20 °C. Improvement of the mechanical properties of BBA alkali- cements with the addition of BSS. Gel phases (C–K–A–S–H) and compact microstructure helps to improve strength. Abstract: In this research the effect of the incorporation of black steel slag (BSS) (25, 50 and 75 wt%) into biomass bottom ash (BBA) as precursor in the synthesis of alkali-activated materials was studied. The alkali-activated pastes were cured at two temperatures, 60 and 20 °C. Thermal curing at 60 °C produced an increase in mechanical properties at early curing ages obtaining similar properties at older ages of 90 days. The addition of up to 50 wt% of BSS resulted in alkali-activated cements with increased compressive and flexural strengths. The increase in mechanical properties could be due to the formation of a higher amount of calcium aluminosilicate gel (C-A-H-S) with respect to potassium aluminosilicate gel (K-A-H-S) or to the synergistic formation of C-K-A-S-H gel. Therefore, these specimens can be used as a binding material for concrete production to replace Portland cement, which can lead to significant environmental and socio-economic improvements by reducing CO2 emissions and consumption of natural resources.